Diamond Shaped Ring Antenna for UWB Applications with Inherent Band-Notched Functionality - Shokri, Majid; Amiri, Zhaleh; Asiaban, Somayeh; Virdee, Bal (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this Letter, a novel printed monopole antenna design is described that operates across a wideband frequency band and exhibits band-notch characteristic necessary to suppress interference signals. The prototype antenna consists of a radiating patch in the configuration of a diamond shaped ring that has attached within it an inverted T-shaped resonant structure that controls the notch frequency. The antenna is excited with a microstrip feed-line and includes an elliptically shaped ground-plane that is defected with a dielectric notch in the vicinity of the patch to enhance the antenna’s impedance bandwidth. The antenna exhibits an inherent stopband function at the WLAN frequency band. The proposed antenna configuration is simple and compact with dimensions of 30×30×1.6 mm3 . The measured impedance bandwidth exceeds the UltraWideband (UWB) spectrum defined between 3.06- 15.96 GHz, for VSWR?2 that corresponds to a fractional bandwidth of 135.6%. The radiation characteristic of the proposed antenna is approximately omni-directional.